A 1D nonlinear TWB model accounting for in plane cross-section deformation. (September 2016) - Gabriele, Stefano; Rizzi, Nicola; Varano, Valerio
Abstract: In this paper a procedure for constructing a 1D continuum equivalent to a Koiter plate, is presented. The result is used to build-up a coarse model of a Thin Walled Beam. The model results to be a nonlinear hyperelastic 1D second gradient continuum, endowed with an internal microstructure described by seven scalar kinematic parameters. The kinematic parameters are able to describe, although in a rough way, the deformation of the TWB in the plane of its cross-section. The nonlinear behaviour of a simply supported strut has been analyzed and the results compared with those given by the commercial finite element code ABAQUS.